Impact of Lung Expansion Therapy Using Positive End-Expiratory Pressure in Mechanically Ventilated Patients Submitted to Coronary Artery Bypass Grafting - Cordeiro,André Luiz Lisboa (2019)
Abstract Objective: To evaluate the impact of different levels of positive end-expiratory pressure (PEEP) on gas exchange in patients undergoing coronary artery bypass grafting (CABG). Methods: A randomized clinical trial was conducted with patients undergoing CABG surgery. Patients were randomized into three groups: Group 10, PEEP of 10 cmH2O; Group 12, PEEP of 12 cmH2O; and Group 15, PEEP of 15 cmH2O. After the randomization, all patients underwent gas analysis at three moments: (1) before lung expansion therapy (LET); (2) 30 minutes after LET; and (3) one hour after extubation. Results: Sixty-six patients were studied, of which 61.7% were men, with mean age of 64 ± 8.9 years. Patients allocated to Group 15 showed a significant improvement in gas exchange comparing pre- and post-expansion values (239±21 vs. 301±19, P<0,001) and the increase was maintained after extubation (278±26). Despite the use of high levels of PEEP, no significant hemodynamic change was evidenced. Conclusion: It is concluded that high levels of PEEP (15 cmH2O) are beneficial for the improvement of gas exchange in patients undergoing CABG.